2021
DOI: 10.1111/dar.13378
|View full text |Cite
|
Sign up to set email alerts
|

Has increasing internet use due to smartphone uptake contributed to the decline in adolescent smoking?

Abstract: Introduction. The emergence of low-cost smartphone technology has coincided with major declines in adolescent smoking and other risk behaviours. This study explores the relationship between internet use and smoking in adolescents and investigates whether rising internet use contributed to the decline in smoking between 2012 and 2018. Methods. Data were drawn from a nationally representative New Zealand survey of students aged 14-15 (N = 11 299), conducted biennially between 2012 and 2018. We used logistic regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Heavy internet users (particularly social users) are more likely to smoke and drink than those who rarely use the internet (Ball et al, 2021;Brunborg and Burdzovic, 2019;de Looze et al, 2019;Iannotti et al, 2009;Koivusilta et al, 2005;Mu et al, 2015;Ng Fat et al, 2021;Vannucci et al, 2020;Vashishtha et al, 2021). Similarly, some studies have found a positive association between computer gaming and substance use (Halkjelsvik et al, 2021;Strizek et al, 2020;Van Rooij et al, 2014), although others have found no association (Ball et al, 2021;Kaur et al, 2020). One study investigated whether a rise in computer gaming was empirically linked to declining adolescent binge drinking in six Nordic countries, and found no association (Halkjelsvik et al, 2021).…”
Section: Increasing Internet Usementioning
confidence: 99%
“…Heavy internet users (particularly social users) are more likely to smoke and drink than those who rarely use the internet (Ball et al, 2021;Brunborg and Burdzovic, 2019;de Looze et al, 2019;Iannotti et al, 2009;Koivusilta et al, 2005;Mu et al, 2015;Ng Fat et al, 2021;Vannucci et al, 2020;Vashishtha et al, 2021). Similarly, some studies have found a positive association between computer gaming and substance use (Halkjelsvik et al, 2021;Strizek et al, 2020;Van Rooij et al, 2014), although others have found no association (Ball et al, 2021;Kaur et al, 2020). One study investigated whether a rise in computer gaming was empirically linked to declining adolescent binge drinking in six Nordic countries, and found no association (Halkjelsvik et al, 2021).…”
Section: Increasing Internet Usementioning
confidence: 99%
“…The health consequences of alcohol consumption were major concerns in many interviews, with discourses of dependence and harm featuring. Similarly, Ball et al [18] found a much stronger focus on health and social risks from drinking in interviews with contemporary teenagers than was present in archival interview data collected between 1999 and 2001. The use of similar methods and interview schedules 20 years apart in this study also drew out important shifts in how young people socialise, with online interactions taking the place of some face-to-face socialising.…”
mentioning
confidence: 98%